Description of post‐implantation embryonic stages in European roe deer (Capreolus capreolus) after embryonic diapause. (27th September 2017) - Beyes, M.; Nause, N.; Bleyer, M.; Kaup, F.‐J.; Neumann, S.
Summary: The embryonic stage of development is defined as the period between fertilization and the establishment of most of the organ systems by the end of this period. Development in this stage is rapid. In many mammalian species, particularly in humans, the interval between fertilization and implantation is exactly determined and continuous without intermission. However, European roe deer ( Capreolus capreolus ) embryos undergo a reversible retardation of development. This interesting reproduction strategy is called embryonic diapause (delayed implantation). After this period of embryonic arrest, development continues without further interruption. The aim of this study was to investigate embryonic development after diapause in European roe deer. Because of the embryonic diapause and the unknown date of fertilization, it was impossible to assign the embryos to a certain gestational age (days). This study describes normal stages of embryonic development mainly based on the external morphological traits of 56 well‐preserved post‐implantation roe deer embryos and attempts to assign the embryos to certain development stages. Carnegie stages of human embryos were used as an orientation for staging roe deer embryos. We observed a considerable range of variation of embryonic stages investigated until the end of January. We found post‐implantation stages of embryonic development already at the end of December and foetuses at the end of January. Moreover, assigning the embryos to a particular stage of development allows the comparison between pairs of twins and triplets. We showed that twins and triplets were always at the same development level, despite the discrepancy in inter‐twin and inter‐triplet size.